Pathologies of power : health, human rights, and the new war on the poor - Farmer, Paul, 1959-2022 (California series in public anthropology, 2003)
Pathologies of Power uses harrowing stories of life--and death--in extreme situations to interrogate our understanding of human rights. Paul Farmer, a physician and anthropologist with twenty years of experience working in Haiti, Peru, and Russia, argues that promoting the social and economic rights of the world's poor is the most important human rights struggle of our times.